Positive pole piece and lithium ion battery comprising same

By controlling the thickness and particle size distribution of the positive electrode active material layer, the ratio of the characteristic peaks of the dQ/dV-V curve of the positive electrode sheet is optimized, and the problem of the reduction of thermal stability and the risk of thermal runaway at high temperatures is solved, and the good fast charging cycle performance of lithium-ion batteries is achieved and the risk of thermal runaway is achieved.

CN119725371APending Publication Date: 2025-03-28CHINA AVIATION LITHIUM BATTERY LUOYANG
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411962445.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials have a risk of reduced thermal stability and thermal runaway at high temperatures, which affects the fast charging and cycling performance and safety of lithium-ion batteries.

Method used

By reasonably controlling the thickness and particle size distribution of the positive electrode active material layer, the ratio of the characteristic peaks of the dQ/dV-V curve of the positive electrode sheet is optimized, so that the lithium-ion battery has good fast charging cycle performance and reduces the risk of thermal runaway.

Benefits of technology

It achieves good fast charging and cycling performance of lithium-ion batteries and low thermal runaway risk, improving the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725371A_ABST
    Figure CN119725371A_ABST
Patent Text Reader

Abstract

The invention discloses a positive pole piece and a lithium ion battery comprising the same, and belongs to the technical field of electrochemistry. The positive pole piece comprises a positive current collector and positive active material layers arranged on two sides of the positive current collector, each positive active material layer comprises a high-nickel ternary positive material as a positive active material, and the positive pole piece meets the following relational expression: (H * RDv) / 10 <-2.5 > * A is greater than or equal to 2.0 and less than or equal to 11.0; h is the thickness of the positive electrode active material layer; rDv is a particle size distribution function of the positive electrode active material; a is a peak area ratio of characteristic peaks in a positive pole piece half-cell charging dQ / dV-V curve. By reasonably controlling the thickness of the positive electrode active material layer and the ratio of the particle size of the positive electrode active material to the characteristic peak in the dQ / dV-V curve of the positive electrode plate, the lithium ion battery containing the positive electrode plate has good fast charge cycle performance, and the risk of thermal runaway is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a positive electrode plate and a lithium ion battery comprising the same. Background Art

[0002] At present, with the continuous development of mobile electronic devices, electric vehicles and other fields, the performance requirements for lithium-ion batteries are becoming higher and higher, including fast charging cycle performance and safety.

[0003] As an important lithium-ion battery material, ternary cathode material (nickel cobalt manganese oxide, NCM) is the main development direction and the mainstream of cathode materials. Nickel is one of the active substances in ternary materials. Increasing the nickel content increases the number of reactive electrons. High-nickel ternary cathode materials have the advantages of high specific energy, low cost and relatively high capacity.

[0004] It is inevitable for batteries to operate and store at high temperatures, especially at higher charging rates. The rate of electrochemical reactions inside the battery increases, which often causes the surface temperature of the pole piece to rise, possibly causing local overheating. However, as the nickel content of ternary materials increases, their thermal stability decreases. High-nickel ternary positive electrode materials may undergo structural changes at high temperatures, resulting in decreased stability of the pole piece, which in turn causes the risk of thermal runaway of the battery.

[0005] Therefore, it is necessary to provide a positive electrode plate with good fast charging cycle performance and low risk of thermal runaway, and a lithium-ion battery containing the same. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode plate and a lithium-ion battery containing the same. The lithium-ion battery containing the positive electrode plate has good fast charging cycle performance and a relatively lower risk of thermal runaway.

[0007] To achieve the above object, in a first aspect of the present invention, a positive electrode plate is provided, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on both sides of the positive electrode current collector, the positive electrode active material layer comprising a chemical formula of LiNi x Co y Mn (1-x-y) O2 positive electrode active material, wherein 0.8≤x<1,0<y<0.2,0<x+y<1;

[0008] The positive electrode sheet satisfies the following relationship:

[0009] 2.0≤(H×R Dv ) / 10-2.5×A≤11.0, where R Dv =2×(D V75-D V 25) / (D V 75+D V 25);

[0010] Wherein, H is the thickness of the positive electrode active material layer when the positive electrode sheet is in a fully charged state, in μm;

[0011] R Dv is the particle size distribution function of the positive electrode active material, D V 25. D V 75 is the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 25% and 75% respectively;

[0012] A is the ratio of the peak area of ​​the main peak between 4.05V and 4.3V to the peak between the initial charging voltage and 3.8V in the dQ / dV-V curve of the positive electrode half-cell charge.

[0013] As a preferred embodiment of the present invention, the positive electrode sheet satisfies the following relationship: 3.0≤(H×R Dv ) / 10-2.5×A≤8.0.

[0014] As a preferred embodiment of the present invention, the range of H is 75 to 130 μm.

[0015] As a more preferred embodiment of the present invention, the range of H is 85 to 110 μm.

[0016] As a preferred embodiment of the present invention, the D V 25 is 1.5~3.0μm, D V 75 is 2.5~12.0μm.

[0017] As a more preferred embodiment of the present invention, the D V 25 is 2.0~2.8μm, D V 75 is 3.5~8.0μm.

[0018] As a preferred embodiment of the present invention, the range of A is 0.2 to 0.68.

[0019] As a more preferred embodiment of the present invention, the range of A is 0.3 to 0.5.

[0020] In a second aspect of the present invention, the present invention provides a lithium-ion battery comprising the positive electrode sheet described above.

[0021] In a third aspect of the present invention, the present invention provides an electronic device comprising the lithium-ion battery described above.

[0022] The beneficial effects of the present invention are:

[0023] The present invention provides a positive electrode plate and a lithium ion battery containing the same. The positive electrode active material in the positive electrode plate of the present invention is a high-nickel ternary positive electrode material, and the thickness of the positive electrode active material layer and the D V 25. D V 75 The ratio of the particle size to the characteristic peak in the dQ / dV-V curve of the positive electrode sheet makes the lithium-ion battery containing the positive electrode sheet have good fast charging cycle performance and reduces the risk of thermal runaway. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the dQ / dV-V curve of the positive electrode half-cell charging of Example 3 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0027] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0028] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0029] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0030] Positive electrode

[0031] An embodiment of the present invention provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a chemical formula of LiNi x Coy Mn (1-x-y) O2 positive electrode active material, wherein 0.8≤x<1,0<y<0.2,0<x+y<1;

[0032] The positive electrode sheet satisfies the following relationship:

[0033] 2.0≤(H×R Dv ) / 10-2.5×A≤11.0, where R Dv =2×(D V 75-D V 25) / (D V 75+D V 25);

[0034] Wherein, H is the thickness of the positive electrode active material layer when the positive electrode sheet is in a fully charged state, in μm;

[0035] R Dv is the particle size distribution function of the positive electrode active material, D V 25. D V 75 is the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 25% and 75%, respectively, in μm;

[0036] A is the ratio of the peak area of ​​the main peak between 4.05V and 4.3V to the peak between the initial charging voltage and 3.8V in the dQ / dV-V curve of the positive electrode half-cell charge.

[0037] For high-nickel (Ni≥0.8) ternary positive electrode materials, during the battery charging process, due to the change in the content of lithium ions, the high-nickel ternary positive electrode materials undergo a series of phase changes: hexagonal phase H1→monoclinic phase M→new hexagonal phase H2→new hexagonal phase H3. Among them, the crystal phase change of H1→M→H2 is reversible, and when the H2 phase changes to the H3 phase, the C-axis direction will undergo partial irreversible contraction, that is, the H2-H3 phase change is irreversible. It should be noted that the H2-H3 phase change of the crystal is unique to high-nickel ternary positive electrode materials, while for ordinary medium and low nickel ternary positive electrode materials (0.5≤Ni<0.8) at the conventional 4.25V voltage, the phase change phenomenon is extremely weak, or even does not occur.

[0038] The charging dQ / dV-V curve of the positive electrode can be used to reflect the above phase change characteristics of the positive electrode active material. The charging dQ / dV-V curve is a differential derivative of the charging capacity of the lithium-ion battery with respect to the voltage, representing the rate of change of capacity with voltage. Among them, dQ represents the capacity change in the battery, and dV represents the voltage change. During the charging process of the lithium-ion battery, Li +When the transition metal ions lose their outermost electrons, the voltage of the positive electrode material rises. Therefore, when the oxidation potentials of Ni, Co, etc. are reached, the ternary material releases a large amount of lithium ions in the corresponding voltage range, contributing to the capacity, and the corresponding peak appears on the dQ / dV-V curve. At this time, the structure of the positive electrode material changes due to the large amount of lithium ions released.

[0039] In the present invention, in the charging dQ / dV-V curve obtained by reorganizing the positive electrode sheet into a single half-cell, the main peak between 4.05 and 4.3V corresponds to the H2-H3 phase transition of the positive electrode active material, and the peak between the initial charging voltage and 3.8V corresponds to the H1-M phase transition of the positive electrode active material. This study found that the cycle stability and thermal runaway risk of the positive electrode sheet are related to the ratio of the peak area between the main peak between 4.05V and 4.3V and the peak between the initial charging voltage and 3.8V in the dQ / dV-V curve of the positive electrode sheet half-cell (i.e., the A value).

[0040] The H1-M phase transition refers to the phase transition from the initial hexagonal phase state (H1 phase) to the intermediate or transition state (M phase). The formation of the M phase is usually associated with the release of lithium ions, accompanied by the expansion of the lattice. In the dQ / dV-V curve, the peak area between the initial charging voltage and 3.8V is relatively large, which may indicate that the electrochemically active Ni 2+ More, H1-M reversible phase transition accounts for a larger proportion.

[0041] When the high-nickel positive electrode active material undergoes the H2-H3 phase transition, the crystal C-axis direction will undergo partial irreversible contraction, and the material structure changes caused by this phase transition will affect the long-term cycle stability of the material. When lithium-ion batteries are rapidly charged at high rates, the rapid charging process will cause this structural change to occur in a shorter period of time, resulting in local strain concentration in the grain boundary region. On the one hand, concentrated local strain may increase the risk of thermal runaway of the battery, and on the other hand, it may further aggravate the oxidative decomposition of the electrolyte on the positive electrode side, thereby affecting the cycle stability of the battery. In addition, under overcharge conditions, the structural changes of the crystal will reduce the stability of the positive electrode sheet, and the risk of the battery swelling, bulging, smoking, or explosion will increase.

[0042] Although the H2-H3 phase transition will bring about irreversible changes in the crystal structure, for high-nickel ternary positive electrode materials, the H2-H3 phase transition should not be too small. A smaller H2-H3 phase transition may mean that the reaction rate of the battery during high-rate rapid charging and discharging is limited, which may reduce the battery's fast charging and high-power discharge performance.

[0043] The difference in oxidation reaction characteristics at different stages will result in different dQ / dV-V peak information. In a specific phase change stage, the rapid reaction zone corresponding to the main characteristic peak is the main reaction stage of delithiation in this phase change stage. The degree of lithium ion migration is high and the potential change amplitude is small. The degree and mode of phase change are the main influencing factors on the stability of the material structure and the rate of delithiation. Changes in the degree and mode of phase change will cause changes in the characteristic peak area. Therefore, this application uses this parameter as an important parameter for evaluating fast charging life and thermal safety capabilities.

[0044] The value of H in the present invention is the thickness of the positive electrode active material layer when the positive electrode plate is in a fully charged state. In the present application, the thickness of the positive electrode active material layer refers to the total thickness of the positive electrode active material layer on the upper and lower surfaces of the current collector in the positive electrode plate, that is, the value of H is equal to the thickness of the positive electrode plate in a fully charged state minus the thickness of the current collector.

[0045] Under different charging states, due to the release of lithium ions, the lattice of the positive electrode active material will change to a certain extent, and then the lattice volume will change, which will cause a certain change in the thickness of the positive electrode active material layer. In the initial stage of charging, lithium ions in the layered structure are continuously released and continuously migrate from the {010} crystal plane, the O-Li-O layer is stretched, so that the unit cell volume expands and the thickness of the pole piece increases. However, as the delithiation proceeds further, the lithium ions in the Li layer are greatly reduced, and the c-axis begins to shrink; at the same time, the stability of the crystal structure skeleton decreases, and the TM mixing and oxygen ion escape further cause the unit cell volume to shrink dramatically and rapidly, and the corresponding positive electrode The thickness of the pole piece is significantly reduced. Compared with low-medium nickel ternary, when charged to the same voltage, high Ni (Ni% ≥ 80%) ternary has a higher degree of delithiation, so the risk of structural expansion-contraction caused by delithiation is greater.

[0046] For lithium-ion batteries, the thickness of the positive electrode active material layer in the positive electrode sheet will have a certain impact on the thermal safety performance and fast charging cycle performance of the battery.

[0047] The positive electrode active material layer should have a certain thickness to ensure the lithium storage capacity of the positive electrode sheet and the appropriate energy density of the battery. However, if the thickness of the positive electrode active material layer is too large, it may increase the diffusion distance of lithium ions in the active material layer, thereby reducing the charge transfer rate and affecting the charge and discharge rate and power performance of the battery; it may also cause the strain accumulation of the positive electrode active material lattice during the charge and discharge process, affecting the cycle stability of the battery; in addition, an overly thick positive electrode active material layer may cause the battery to generate a lot of heat during the charge and discharge process, increasing the risk of thermal runaway. When the thickness of the positive electrode active material layer is thin, that is, the H value is small, the positive electrode active material particles inside the positive electrode active material layer have relatively more exposed active sites, which are easier to contact with the electrolyte, resulting in oxidative decomposition of the electrolyte and release of heat. This situation will also increase the risk of thermal runaway in lithium-ion batteries.

[0048] For the positive electrode plate of the present invention, the particle size distribution of the positive electrode active material is also an important factor affecting the fast charge cycle performance and thermal safety.

[0049] In the present invention, R is defined as Dv is the particle size distribution function of the positive electrode active material, R Dv =2×(D V 75-D V 25) / (D V 75+D V 25) R Dv It's about D V 75 particle size and D V 25 The parameters of particle size reflect the relative difference of particle size distribution width, including particle size distribution width, particle size distribution symmetry, and D V 75 and D V The size of the particles is 25, and the weight of the size difference is introduced.

[0050] Under the appropriate particle size distribution width, the particle size of the positive electrode active material has a certain consistency, which helps to reduce the non-uniformity of the electrochemical reaction and regional stress concentration in the battery's charge and discharge cycle, improve the battery's cycle stability, and reduce the risk of thermal runaway. The positive electrode active material has an appropriate particle size distribution symmetry, which helps the large and small particles of the positive electrode active material to cooperate with each other, thereby improving the structural stability of the positive electrode sheet and improving the thermal safety of the battery.

[0051] This study found that by controlling R Dv The value of D V 75 particle size and D V The particle size of the positive electrode active material can be comprehensively regulated to ensure that the particle size grading of the positive electrode active material is appropriate, the overall size of the positive electrode active material is appropriate, the difference in particle size between large and small particles is appropriate, and the symmetry is appropriate, which is conducive to better fast charging cycle performance of lithium-ion batteries and lower risk of thermal runaway.

[0052] For positive electrode sheets using high-nickel ternary materials as positive electrode active materials, the size of its A value is related to many factors, such as the chemical structure, particle size distribution, morphology, coating, etc. of the positive electrode active materials, as well as the compaction density, thickness, surface roughness, porosity, etc. of the positive electrode active material layer. Considering the influence between the A value of the positive electrode sheet, the thickness of the positive electrode active material layer, and the particle size of the positive electrode active material, it is difficult to improve the overall performance of the positive electrode sheet by controlling a single parameter.

[0053] The present invention comprehensively controls the thickness of the positive electrode active material layer and the D V 25. D V75 particle size and the area ratio of the peaks from 4.05 to 4.3 V to the peaks from the initial charging voltage to 3.8 V in the dQ / dV-V curve of the positive electrode, so that the positive electrode satisfies the relationship: 2.0≤(H×R Dv ) / 10-2.5×A≤11.0, the lithium-ion battery containing the positive electrode sheet has good fast charging cycle performance and reduces the risk of thermal runaway.

[0054] Exemplarily, in the present invention, (H×R Dv ) / 10-2.5×A can have a value of 2.0, 2.2, 2.5, 3.5, 4., 5.0, 6.0, 7.0, 7.5, 8.0, 8.5, 9.0, 10.0, 10.5, 11.0, or it can be an interval formed by any two of the above values.

[0055] In one embodiment, the positive electrode sheet satisfies the following relationship: 3.0≤(H×R Dv ) / 10-2.5×A≤8.0.

[0056] When the positive electrode sheet satisfies the above preferred relationship, Dv The comprehensive control of , H and A is relatively more suitable, the risk of thermal runaway of the positive electrode plate containing this is relatively lower, and the fast charging cycle performance is relatively better.

[0057] In one embodiment, the range of H is 75 to 130 μm. For example, H may be 75 μm, 95 μm, 105 μm, 110 μm, 120 μm, or 130 μm.

[0058] In one preferred embodiment, the range of H is 85-110 μm.

[0059] The present invention does not limit the detection of the H value, and those skilled in the art can detect the thickness of the positive electrode active material layer when the positive electrode sheet is in a fully charged state according to conventional technical means. Exemplarily, the following method can be used to detect the H value:

[0060] The positive electrode and lithium metal are reassembled into a monolithic half-cell. The monolithic half-cell is activated at 0.2C for two cycles in a voltage window of 2.8-4.3V, then charged at a constant current of 0.5C to a voltage of 4.3V, and then charged at a constant voltage to a current of 0.04C.

[0061] In an environment of about 25°C, the positive electrode sheet in a fully charged state in the lithium-ion battery is removed, and the electrolyte remaining on the surface of the positive electrode sheet is wiped off with dust-free paper; the positive electrode sheet is then placed under plasma for cutting to obtain its cross section; the cross section of the positive electrode sheet is observed under SEM, and the total thickness of the sheet is H1μm and the thickness of the current collector is H2μm, with adjacent test points spaced 2cm to 3cm apart, at least 8 different points are tested, the thickness of all test points is recorded, and the average value of these test points H1-H2 is calculated, and the average value is used as the thickness of the positive electrode active material layer Hμm.

[0062] The thickness of the positive electrode active material can be controlled by adjusting the coating amount of the positive electrode slurry, the rolling conditions of the positive electrode sheet, and using positive electrode active materials of different specifications.

[0063] Generally speaking, the thickness of the positive active material layer in the positive electrode sheet is generally 50-200μm. This study found that when the range of H is 75-130μm, especially when the range of H is 85-110μm, the thermal runaway risk and fast charging cycle performance of the positive electrode sheet after being applied to lithium-ion batteries are better.

[0064] In one embodiment, the D V 25 is 1.5 to 3.0 μm, for example, the D V 25 can be 1.5μm, 1.8μm, 2.0μm, 2.4μm, 2.6μm, 2.8μm, or 3.0μm.

[0065] In one embodiment, the D V 75 is 2.5 to 12.0 μm, for example, the D V 75 can be 2.5μm, 2.8μm, 3.0μm, 4.0μm, 6.0μm, 8.0μm, 10.0μm, 11.0μm, 11.5μm, 12.0μm.

[0066] In one preferred embodiment, the D V 25 is 2.0 to 2.8 μm, and D V 75 is 3.5~8.0μm.

[0067] About D V 25 and D V The present invention does not limit the detection method of D 75 of the positive electrode active material. Those skilled in the art can use conventional technical means to detect the D V 25 and D V 75 for detection. For example, it can be measured by using a laser particle size analyzer, for example, a Master sizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.

[0068] The particle size of positive electrode active materials is generally regulated by graded screening. There is no special restriction on the specific graded screening method, which can be selected according to the actual situation. Generally, screen graded screening is used. The positive electrode active material is put into screens of different mesh levels for screening. Due to the different particle sizes of the particles, small particles will be screened out by the screen, while the required particle size can be retained on the screen, thereby obtaining positive electrode active materials of different particle size grades. According to actual needs, active materials of certain particle sizes can be allocated so that their particle size distribution can be artificially adjusted.

[0069] In the above D V 25 and D V 75, the particle size distribution width and particle size distribution symmetry of the positive electrode active material particles are appropriate, the overall size of the positive electrode active material is appropriate, and the positive electrode active material has an appropriate relative difference in particle size distribution width.

[0070] In one embodiment, the range of A is 0.2 to 0.68. For example, A may be 0.2, 0.28, 0.36, 0.44, 0.57, 0.63, or 0.68.

[0071] In one preferred embodiment, the range of A is 0.3 to 0.5.

[0072] The present invention does not limit the detection method of the A value. Those skilled in the art can detect the positive electrode sheet according to conventional technical means to obtain a dQ / dV-V curve. Exemplarily, the following method can be used: the positive electrode sheet and lithium metal are recombined into a single half-cell, activated at 0.2C for two cycles in a voltage window of 2.8-4.3V, charged at a constant current of 0.33C between the voltage range of 2.8-4.3V, and discharged at a constant current of 0.33C to obtain a charging dQ / dV-V curve; the peak area of ​​the peak between 4.05 and 4.3V in the dQ / dV-V curve is A. H2-H3 The peak area of ​​the peak between the initial charging voltage and 3.8V in the dQ / dV-V curve is A H1-M , A=A H2-H3 / A H1-M .

[0073] Since the value of A is related to the chemical structure, particle size distribution, morphology, coating condition, and compaction density, thickness, surface roughness, porosity, etc. of the positive electrode active material, the value of A can be controlled by changing the positive electrode active material and adjusting the preparation process of the positive electrode sheet.

[0074] When the A value is within the above preferred range, the positive electrode active material has a suitable H2-H3 phase transition, the electrochemical reaction activity of the positive electrode plate is good, the battery has better high-rate rapid charge and discharge performance, the positive electrode plate has good cycle stability, and the battery has a lower risk of thermal runaway.

[0075] In the present invention, for LiNi x Co y Mn (1-x-y) The preparation method of O2 is not limited, and those skilled in the art can prepare the positive electrode active material according to conventional technical means. Exemplarily, the positive electrode active material precursor and the lithium source are mixed and sintered to obtain the positive electrode active material.

[0076] In some embodiments of the present invention, the sintering process may further include grinding and crushing; wherein the crushing may include gas crushing or roller crushing.

[0077] The positive electrode active material precursor may be one or more of oxides, hydroxides and carbonates containing Ni, Co and Mn in a stoichiometric ratio, for example, a hydroxide containing Ni, Co and Mn in a stoichiometric ratio. The positive electrode active material precursor may be obtained by methods known in the art, for example, by coprecipitation, gelation or solid phase method.

[0078] In some embodiments of the present invention, the Ni source includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate or nickel acetate; and / or the Co source includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate or cobalt acetate; and / or the Mn source includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate or manganese acetate; and / or the Li source includes at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3) or lithium nitrate (LiNO3).

[0079] The positive electrode active material precursor and the lithium source can be mixed by a ball mill mixer or a high-speed mixer. The mixed materials are added to an atmosphere sintering furnace for sintering. The sintering atmosphere is an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere. In some embodiments of the present invention, the sintering process can be selected as constant temperature sintering, gradient sintering or multiple sintering as needed.

[0080] In addition, the positive electrode active material can also be coated or doped. Specifically, the coating modification can be to coat the coating material on the surface of the positive electrode active material by dry coating (high temperature solid phase method), and the surface of the positive electrode active material is partially or completely coated with a coating layer containing the coating element; the doping modification can be to add a doping element source containing the doping element when preparing the positive electrode active material. The coating element or the doping element is independently selected from at least one of aluminum (Al), titanium (Ti), tungsten (W), boron (B), phosphorus (P), zirconium (Zr), yttrium (Y) and silicon (Si). The doping element source containing the doping element can be a compound containing the doping element. For example, when the doping element is aluminum, the doping element source can be aluminum trioxide; when the doping element is tungsten, the doping element source can be tungsten trioxide; when the doping element is zirconium, the doping element source can be zirconium oxide; when the doping element is boron, the doping element source can be boron trioxide.

[0081] The positive electrode active material layer may further include a conductive agent and a binder in addition to the above-mentioned positive electrode active material.

[0082] The conductive agent is used to provide conductivity in the electrode. Any conductive agent can be used without particular limitation as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Preferred are carbon materials such as carbon nanofibers, carbon blacks such as acetylene black and Ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes.

[0083] The binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Therefore, in the embodiment, the binder suitable for use is a fluorinated polyolefin binder, which may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (e.g., carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.

[0084] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0085] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art. For example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.

[0086] Lithium-ion battery

[0087] An embodiment of the present invention provides a lithium-ion battery, which includes the positive electrode sheet, negative electrode sheet, and electrolyte solution described above.

[0088] The negative electrode sheet of the present invention includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a conductive agent and / or a binder.

[0089] The present invention places no particular limitation on the negative electrode current collector, as long as it has high electrical conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, or silver, or an aluminum-cadmium alloy can be used.

[0090] Regarding the negative electrode active material, the embodiment of the present invention does not specifically limit the type of the negative electrode active material, and it can be selected according to actual needs. As an example, the negative electrode active material can be one or more of natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiOm (0 < m < 2, such as m = 1), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithium titanate Li4Ti5O 12 , Li-Al alloy, and metallic lithium.

[0091] The embodiment of the present invention does not specifically limit the types of the conductive agent and the binder in the negative electrode active material layer, and they can be selected according to actual needs. As an example, the conductive agent is one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder is one or more of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, water-based acrylic resin, and carboxymethyl cellulose. The negative electrode active material layer may also optionally include a thickening agent, such as carboxymethyl cellulose.

[0092] The electrolyte solution of the present invention can be various electrolyte solutions applicable to electrochemical energy storage devices in the art. The electrolyte solution includes an electrolyte and a solvent, and the electrolyte generally includes a lithium salt.

[0093] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5 to 5 mol / L.

[0094] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE). Based on the weight of the electrolyte, the weight content of the solvent can be 70-98%.

[0095] In addition, the electrolyte may further include additives. Specifically, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0096] The lithium-ion battery may also include a diaphragm, which is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.

[0097] Electronic Devices

[0098] An embodiment of the present invention provides an electronic device, comprising the lithium-ion battery described above. The lithium-ion battery serves as a power supply for the electronic device.

[0099] The electronic device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0100] The present invention is further described below with specific embodiments:

[0101] Example 1

[0102] Embodiment 1 provides a lithium ion battery, and the preparation method is as follows:

[0103] (1) Preparation of positive electrode sheet

[0104] (1.1) According to LiNi x Co 0.02 Mn 1-0.02-x The molar ratio of each element Li, Ni, Co, and Mn in the chemical formula of O2 is respectively weighed nickel sulfate, cobalt sulfate, manganese sulfate, and lithium hydroxide, wherein lithium hydroxide is slightly excessive. Specifically, the value of x is shown in Table 1, and the ratio of the molar amount of lithium hydroxide to the total molar amount of nickel sulfate, cobalt sulfate, and manganese sulfate (Li / Me) is shown in Table 1;

[0105] (1.2) nickel sulfate, cobalt sulfate and manganese sulfate are dissolved in deionized water respectively, and each metal solution is transported to a reactor through a pipeline to form a mixed metal solution, and nitrogen is introduced as a protective gas, and a NaOH aqueous solution is added to the mixed metal solution as a precipitant, and ammonia water is added as a complexing agent. The concentration and amount of ammonia water in the solution are adjusted to control the pH value of the solution to 11, and the reaction is carried out for 5 hours. The product is filtered and dried at 105° C. to obtain a ternary precursor;

[0106] (1.3) After the ternary precursor and lithium hydroxide are uniformly mixed, a certain amount of a doping element source containing a doping element is weighed as needed, and 70 wt.% of the doping element source is added, and the mixture is stirred and mixed at 80° C. and 500 rpm; the type of the doping element is shown in Table 1 (in Example 1, aluminum and the doping element source is aluminum oxide), and the weighing amount of the doping element source is calculated according to the weight ratio of the doping element to the mixture of the ternary precursor and lithium hydroxide, specifically shown in Table 1 (in Example 1, 2800 ppm);

[0107] After mixing, sintering is carried out. The primary sintering atmosphere is an oxygen-containing atmosphere (oxygen flow rate is 130m 3 / h), the temperature and time of the first sintering are shown in Table 1;

[0108] (1.4) The material after the primary sintering was cooled, washed with water, and dried, and then the remaining 30wt.% of the doping element source was added and mixed at 150°C and 300rpm; and then a secondary sintering was performed in an oxygen-containing atmosphere (oxygen flow rate was 110m 3 / h), the secondary sintering temperature is 600℃ and the time is 5h;

[0109] (1.5) The secondary sintered product is ground and gas-crushed. The gas-crushing time is shown in Table 1. After gas-crushing, the product is screened to obtain the product that meets D in Table 2. V 25 and D V 75 particle size distribution of ternary positive electrode active materials;

[0110] (1.6) The positive electrode active material, binder (polyvinylidene fluoride), and conductive agent (carbon black) are mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone (NMP) is added. The mixture is stirred in a vacuum mixer until the mixture becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the positive electrode collector (aluminum foil, thickness of 12 μm); the positive electrode collector coated with the positive electrode slurry is transferred to an oven for drying, and then rolled and cut into positive electrode sheets.

[0111] (2) Preparation of negative electrode sheet

[0112] The negative electrode active material (artificial graphite), conductive agent (CNT), thickener (carboxymethyl cellulose, CMC), and binder (styrene-butadiene rubber, SBR) are mixed in a mass ratio of 96:2:1:1, and the negative electrode slurry is made by a wet process using a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode collector (copper foil), and the negative electrode collector coated with the negative electrode slurry is transferred to an oven for drying, and then rolled and cut to obtain the negative electrode sheet.

[0113] (3) Preparation of electrolyte

[0114] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a weight ratio of 1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0115] (4) Preparation of diaphragm

[0116] A polyethylene (PE) diaphragm coated with ceramic and polyvinylidene fluoride is used.

[0117] (5) Preparation of batteries

[0118] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.

[0119] Examples 2 to 13, Comparative Examples 1 to 3

[0120] Examples 2 to 13 and Comparative Examples 1 to 3 provide a lithium ion battery respectively, and the preparation method is similar to that of Example 1, except that:

[0121] Example 2, Comparative Example 1 When preparing the positive electrode sheet, the values ​​of Li / Me, x, the doping elements and the weighing amount, the temperature and time of the primary sintering are controlled as shown in Table 1, and in step (1.5), gas crushing is not performed, but multi-stage continuous roller crushing is performed to screen out the positive electrode sheet that meets the requirements of D in Table 2. V 25 and D V 75 particle size distribution of ternary positive electrode active materials;

[0122] In the preparation of the positive electrode sheets in Examples 3 to 9, Example 11 and Comparative Example 2, the values ​​of Li / Me, x, the doping elements and the weighing amount, the temperature and time of the primary sintering, and the gas crushing time are controlled as shown in Table 1, and the positive electrode sheets meeting the requirements of D in Table 2 are screened in step (1.5). V 25 and D V 75 particle size distribution of ternary positive electrode active materials;

[0123] Example 12 When preparing the positive electrode sheet, the values ​​of Li / Me, x, the doping elements and their weight, the temperature and time of the primary sintering, and the gas crushing time are controlled as shown in Table 1, and no doping element source is added in step (1.3), but all 100 wt.% of the doping element source is added in step (1.4) and mixed; at the same time, in step (1.5), the element satisfying D in Table 2 is screened. V 25 and D V 75 particle size distribution of ternary positive electrode active materials;

[0124] In Example 10, Example 13 and Comparative Example 3, no doping element is added when preparing the positive electrode sheet. Therefore, in steps (1.3) and (1.4), the doping element source is not mixed, and the primary sintering and secondary sintering are directly performed; at the same time, the values ​​of Li / Me, x, the temperature and time of the primary sintering, and the gas breaking time are controlled as shown in Table 1, and in step (1.5), the D in Table 2 is screened. V 25 and D V 75 particle size distribution of ternary positive electrode active materials.

[0125] In addition, in each embodiment and comparative example of the present invention, by controlling the conditions of positive electrode slurry coating and rolling, and combining the use of different positive electrode active materials, the thickness of the positive electrode active material layer of the positive electrode sheet when in a fully charged state is adjusted to meet the requirements shown in Table 2.

[0126] Table 1

[0127]

[0128]

[0129] For each embodiment and comparative example, the thickness of the positive electrode active material layer (H), the particle size distribution function of the positive electrode active material (R Dv ), in the positive electrode half-cell charging dQ / dV-V curve, the peak area ratio (A) of the peak between 4.05 and 4.3 V and the peak between the initial charging voltage and 3.8 V is as shown in Table 2. The detection methods of the above items are as follows:

[0130] H: The positive electrode and lithium metal are recombined into a monolithic half-cell. The monolithic half-cell is activated at 0.2C for two cycles in a voltage window of 2.8-4.3V, then charged at a constant current of 0.5C to a voltage of 4.3V, and then charged at a constant voltage to a current of 0.04C;

[0131] In an environment of about 25°C, the positive electrode sheet in a fully charged state in the lithium-ion battery is removed, and the electrolyte remaining on the surface of the positive electrode sheet is wiped off with dust-free paper; the positive electrode sheet is then placed under plasma for cutting to obtain its cross section; the cross section of the positive electrode sheet is observed under SEM, and the total thickness of the sheet is H1μm and the thickness of the current collector is H2μm, with adjacent test points spaced 2cm to 3cm apart, at least 8 different points are tested, the thickness of all test points is recorded, and the average value of these test points H1-H2 is calculated, and the average value is used as the thickness of the positive electrode active material layer Hμm.

[0132] R Dv , D V 25. D V 75: dismantle the empty lithium-ion battery to obtain the lithium-embedded positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15%; scrape off the positive electrode active material layer on the surface of the current collector, calcine it at 500°C for 3 hours to remove the conductive agent, binder, surface side reaction products, and residual electrolyte, and finally grind and sieve (150 mesh) to obtain the positive electrode active material;

[0133] The positive electrode active material was dispersed in an aqueous solution containing 3% sodium hexametaphosphate dispersant, and after continuous stirring with a glass rod for 10 circles, all the samples were quickly poured into the test sample pool of a particle size distribution instrument (Master sizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK) for testing to obtain D V 25. D V 75, in μm; R Dv =2×(D V 75-D V 25) / (D V 75+D V 25).

[0134] A: The positive electrode and lithium metal are recombined into a single half-cell, activated at 0.2C for two cycles in the voltage window of 2.8-4.3V, charged at 0.33C constant current in the voltage range of 2.8-4.3V, and discharged at 0.33C constant current to obtain the charging dQ / dV-V curve;

[0135] The peak area between 4.05 and 4.3 V in the dQ / dV-V curve is A. H2-H3 The peak area of ​​the peak between the initial charging voltage and 3.8V in the dQ / dV-V curve is A H1-M , A=A H2-H3 / A H1-M .

[0136] Figure 1 The dQ / dV-V curve of the positive electrode half-cell of Example 3, where the initial charging voltage is 3.3V, A H1-M Equivalent to the peak area between 3.3V and 3.8V (as shown by the circle in the figure), A H2-H3 It is the peak area of ​​the main peak located between 4.05 and 4.3 V.

[0137] Table 2

[0138]

[0139]

[0140] The performance of the lithium-ion batteries prepared in the above embodiments and comparative examples was tested. The specific items and methods are as follows. The results are shown in Table 3.

[0141] (1) Fast charging cycle life:

[0142] Use a battery charge and discharge tester to test the lithium-ion battery at 45°C. First, fully charge with 0.33C constant current and constant voltage (4.25V & 0.05C cut-off), discharge with 0.33C constant current to 2.75V, and cycle for 2 weeks to fix the capacity. Then start the fast charge cycle, and the cycle system is as follows: charge with 0.33C constant current to 60% SOC, then charge with 3C constant current to 4.25V cut-off, then reduce the charge rate to 2.8C constant current, still with 4.25V cut-off; subsequently, continue to charge with 0.2C as a step, charge to 4.25V cut-off, then downgrade the charge until it drops to 0.2C and then charge with 0.05C constant current to 4.25V full charge. After standing for 5 minutes, the battery is discharged to 2.75V at a constant current of 1C. This is one cycle. As the battery cycles, the battery capacity continues to decay. When the capacity decays to 80% of the initial discharge capacity, the number of cycles experienced is recorded as the fast charging cycle life of the battery.

[0143] (2) Thermal runaway temperature:

[0144] At 25°C, charge the lithium-ion battery at a constant current of 1C to 4.2V, and further charge at a constant voltage of 4.2V to a current of 0.05C; disassemble the lithium-ion battery, take out the positive electrode sheet separately, weigh it, roll it up, fold it in half and put it into the battery packaging bag; add the corresponding amount of electrolyte to ensure that the electrolyte retention is 3g; vacuum seal the battery packaging bag to form a battery cell, and leave it for more than 6 hours to ensure that the positive electrode sheet can be fully soaked in the electrolyte; then put the battery cell into a safe hot box, start heating from 25°C at a rate of 1°C / min, and monitor the change in surface temperature of the battery cell; among which, the furnace temperature corresponding to the maximum temperature rise rate of the battery cell is the thermal runaway temperature of the battery cell.

[0145] Table 3

[0146]

[0147]

[0148] For the lithium-ion batteries prepared in the embodiments of the present invention, the high-temperature fast-charging cycle life is ≥620, and can reach up to 890 cycles, and the thermal runaway temperature is ≥140°C, and it has excellent high-temperature safety performance and fast-charging cycle performance.

[0149] According to the test results of Comparative Examples 1 to 3, when the positive electrode sheet (H×R Dv When the value of ) / 10-2.5×A exceeds the range of 2.0 to 11.0, the high-temperature stability of the lithium-ion battery containing the positive electrode plate is poor, the fast-charging cycle life is low, and the thermal runaway temperature of the lithium-ion battery is also too low.

[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on both sides of the positive electrode current collector, characterized in that: The positive electrode active material layer comprises a chemical formula of LiNi x Co y Mn (1-x-y) O2 positive electrode active material, wherein 0.8≤x<1, 0<y<0.2, 0<x+y<1; The positive electrode sheet satisfies the following relationship: 2.0≤(H×R Dv ) / 10-2.5×A≤11.0, where R Dv =2×(D V 75-D V 25) / (D V 75+D V 25); Wherein, H is the thickness of the positive electrode active material layer when the positive electrode sheet is in a fully charged state, in μm; R Dv is the particle size distribution function of the positive electrode active material, D V 25. D V 75 is the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 25% and 75% respectively; A is the ratio of the peak area of ​​the main peak between 4.05V and 4.3V to the peak between the initial charging voltage and 3.8V in the dQ / dV-V curve of the positive electrode half-cell charge.

2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode sheet satisfies the following relationship: 3.0≤(H×R Dv ) / 10-2.5×A≤8.

0.

3. The positive electrode sheet according to claim 1, characterized in that: The range of H is 75 to 130 μm.

4. The positive electrode sheet according to claim 3, characterized in that: The range of H is 85 to 110 μm.

5. The positive electrode sheet according to claim 1, characterized in that: The D V 25 is 1.5~3.0μm, D V 75 is 2.5~12.0μm.

6. The positive electrode sheet according to claim 5, characterized in that: The D V 25 is 2.0~2.8μm, D V 75 is 3.5~8.0μm.

7. The positive electrode sheet according to claim 1, characterized in that: The range of A is 0.2 to 0.

68.

8. The positive electrode sheet according to claim 7, characterized in that: The range of A is 0.3 to 0.

5.

9. A lithium ion battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 1 to 8.

10. An electronic device, characterized in that: A lithium-ion battery comprising the lithium-ion battery of claim 9.

Citation Information

Cited By

  • Battery cell, battery device, and electric device

    CN122417990A